A catalogue of stellar diameters and fluxes for mid-infrared interferometry. Issue 3 (7th October 2019) - Cruzalèbes, P; Petrov, R G; Robbe-Dubois, S; Varga, J; Burtscher, L; Allouche, F; Berio, P; Hofmann, K-H; Hron, J; Jaffe, W; Lagarde, S; Lopez, B; et al.
Abstract: We present the Mid-infrared stellar Diameters and Fluxes compilation Catalogue (MDFC) dedicated to long-baseline interferometry at mid-infrared wavelengths (3–13 μ m). It gathers data for half a million stars, i.e. nearly all the stars of the Hipparcos -Tycho catalogue whose spectral type is reported in the SIMBAD data base. We cross-match 26 data bases to provide basic information, binarity elements, angular diameter, magnitude and flux in the near and mid-infrared, as well as flags that allow us to identify the potential calibrators. The catalogue covers the entire sky with 465 857 stars, mainly dwarfs and giants from B to M spectral types closer than 18 kpc. The smallest reported values reach 0.16 μ Jy in L and 0.1 μ Jy in N for the flux, and 2 microarcsec for the angular diameter. We build four lists of calibrator candidates for the L and N bands suitable with the Very Large Telescope Interferometer (VLTI) sub- and main arrays using the MATISSE instrument. We identify 1621 candidates for L and 44 candidates for N with the Auxiliary Telescopes (ATs), 375 candidates for both bands with the ATs, and 259 candidates for both bands with the Unit Telescopes (UTs). Predominantly cool giants, these sources are small and bright enough to belong to the primary lists of calibrator candidates. In the near future, we plan to measure their angular diameter with 1 per cent accuracy.